Optimizing real-time PCR method to detect Leptospira spp. in human blood and urine specimens (Medical Journal of Indonesia, 2012)
Background: Leptospirosis is an acute infectious disease in humans caused by Leptospira spp. and classified as a zoonosis. Clinical symptoms of leptospirosis are nonspecific and the current available laboratory method for detecting Leptospira spp. is difficult, which resulted to the misdiagnosis of this disease. Therefore, the rapid and accurate method is needed to diagnose the disease. This study was aimed to optimize molecular diagnostic test using real-time PCR assay as a rapid, sensitive and specific method for the detection of pathogenic Leptospira spp. in humans. Methods: Bacterial DNA was extracted by DNA extraction kit according to the manufacturer's instructions. Primers and probes used in this study was based on previous and published research. The assay is performed using PCR-IQTM5, iCycler Multicolor real-time PCR detection system. Specificity of the primer used was evaluated towards some bacterial pathogens. Results: Limit detection of the DNA was 0.375 fg/ml and the primers used does not cross-react with the genomes of the pathogens tested. Limit detection of DNA in blood is 150 fg/μl, and in urine is 1470 fg/μl. Conclusion: Real-time PCR test is a rapid and accurate method for detecting pathogenic Leptospira spp. in human specimens. Further research is needed to determine the sensitivity and specificity of real-time PCR tests compared with other diagnostic methods in clinical settings. (Med J Indones 2012;21:13-7) Keywords: Leptospirosis, Leptospira, optimization, real-time PCR